Occupational exposures in the oil and gas extraction industry: State of the science and research recommendations. Issue 7 (14th March 2014) - Witter, Roxana Z.; Tenney, Liliana; Clark, Suzanne; Newman, Lee S.
<x xml:space="preserve">Abstract</x> The oil and gas extraction industry is rapidly growing due to horizontal drilling and high volume hydraulic fracturing (HVHF). This growth has provided new jobs and economic stimulus. The industry occupational fatality rate is 2.5 times higher than the construction industry and 7 times higher than general industry; however injury rates are lower than the construction industry, suggesting injuries are not being reported. Some workers are exposed to crystalline silica at hazardous levels, above occupational health standards. Other hazards (particulate, benzene, noise, radiation) exist. In this article, we review occupational fatality and injury rate data; discuss research looking at root causes of fatal injuries and hazardous exposures; review interventions aimed at improving occupational health and safety; and discuss information gaps and areas of needed research. We also describe Wyoming efforts to improve occupational safety in this industry, as a case example. Am. J. Ind. Med. 57:847–856, 2014. © 2014 Wiley Periodicals, Inc.